2013
DOI: 10.1093/ntr/ntt128
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the Understanding of Craving During Smoking Cessation Attempts: A Demonstration of the Time-Varying Effect Model

Abstract: Advancing the understanding of smoking cessation requires a complex and nuanced understanding of behavior change. To this end, ecological momentary assessments (EMA) are now being collected extensively. The time-varying effect model (TVEM) is a statistical technique ideally suited to model processes that unfold as behavior and nicotine dependence change. Coefficients are expressed dynamically over time and are represented as smooth functions of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
82
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 38 publications
1
82
0
1
Order By: Relevance
“…Investigations reported a consistent positive correlation between negative affect and tobacco craving (Berkman et al, 2011a;Delfino et al, 2001;Dunbar et al, 2010;Ferguson et al, 2006;Lanza et al, 2014;McCarthy et al, 2006;O'Connell et al, 2000O'Connell et al, , 2004Shiyko et al, 2012Shiyko et al, , 2014Whalen et al, 2001). One study reported a decreased association between craving and negative affect over time following quitting (Shiyko et al, 2012).…”
Section: Intra-individual Variablesmentioning
confidence: 99%
“…Investigations reported a consistent positive correlation between negative affect and tobacco craving (Berkman et al, 2011a;Delfino et al, 2001;Dunbar et al, 2010;Ferguson et al, 2006;Lanza et al, 2014;McCarthy et al, 2006;O'Connell et al, 2000O'Connell et al, , 2004Shiyko et al, 2012Shiyko et al, , 2014Whalen et al, 2001). One study reported a decreased association between craving and negative affect over time following quitting (Shiyko et al, 2012).…”
Section: Intra-individual Variablesmentioning
confidence: 99%
“…We used logistic TVEM [17] to examine how our predictors were associated with the odds of HED and harms from ages 16 to 28 years. TVEMs were fit using the logistic_TVEM SAS macro [34].…”
Section: Planned Analysesmentioning
confidence: 99%
“…TVEMs were fit using the logistic_TVEM SAS macro [34]. TVEM flexibly estimates how the association between a predictor and outcome differs as a function of age without assuming that the association follows a parametric function of time [17]. TVEM uses all available data for every individual over time; thus, time-specific observations with missing values are excluded from the model at that time point [30].…”
Section: Planned Analysesmentioning
confidence: 99%
See 2 more Smart Citations